Tunable SAW Devices Based on Ni:ZnO/ZnO/GaN Structures with Buried IDTs. (28th October 2017) - Li, Rui; Reyes, Pavel Ivanoff; Li, Guangyuan; Tang, Ke; Yang, Keyang; Wang, Szu-Ying; Han, Jingjing; Emanetoglu, Nuri William; Lu, Yicheng
Abstract : Tunable RF devices have promising applications in low-power resettable sensors, adaptive signal processing, and secure wireless communications. We report a tunable surface acoustic wave (SAW) device built on a multifunctional ZnO/GaN-based structure. The device consists of a piezoelectric Ni:ZnO (NZO) layer deposited on the top of a ZnO/GaN semiconductor heterostructure. The multifunctional ZnO layers are made through a hybrid deposition technique: RF sputtering of a piezoelectric NZO layer and metallorganic chemical vapor deposition (MOCVD) of a semiconducting n-type ZnO layer on the GaN/Al2 O3 substrate. This multifunctional and multilayer structure combines the large electromechanical coupling coefficient of ZnO and high acoustic velocities of GaN. The unique dispersion relationship in ZnO/GaN enables high-frequency (GHz) operation using higher order SAW modes. Two device configurations are designed: one with the interdigital transducer (IDT) exposed on the NZO surface, and one with the IDT buried inside NZO layer. Both devices operate at the GHz frequency. SAW frequency tuning is achieved by voltage controlled acoustoelectric interaction. The device using the buried IDT structure has better performance over the counterpart with exposed IDT SAW. The ZnO/GaN-based tunable SAW device with buried IDTs operating at 1.35 GHz has frequency tunability of ∼0.9% at low biasing voltage range (−12 V∼0 V).